Governance and networking in the Third Sector of Social Action - López García, Irene María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
AA The Spanish Third Sector of Social Action is a key agent for the promotion of inclusion in the European social model. Its strength lies in the internal alliances between entities, as well as the establishment of links with the state and the market. It will be shown, through documentary analysis of secondary sources. the situation in which both types of governance are with regard to policies for inclusion in the EU. The results show a progression in terms of structures, channels, ideas and common goals, but also deficits that point the way forward towards collaboration and participation.